Comparison of General Anesthesia and Regional Anesthesia for Caesarean Section - Abdullah Hassan Salah Alghamdi Albaraa Abdulrhman IAlnafisi, BADR MUIDH A ALHARBI, Hassan Ahmed Khayat, SHADI shareef alammri; Albaraa saeedalradaddi, zyad assad m altrazi, Taher Mohammed Yaseen Bantan, Luay hesham Mohammed Hafiz, Mohammad Abdullah Arif (Journal of International Crisis and Risk Communication Research, 2024)
Objective: To compare the maternal and neonatal outcomes when two different types of anesthesia, either general or regional, are administered for cesarean section. Design: It is a comparative study. Setting: The research was conducted in the Dicle University Gynecology and Obstetrics Clinic, in Sehit Surgical Hospital, and in Cumhuriyet Ana Family Health Center in Diyarbakir, from June 1999 to December 2000. Subjects: Two hundred and twenty-eight patients who underwent cesarean section. Interventions: General anesthesia had been applied to 113 (49.5%) patients and regional anesthesia to 115 (50.5%) patients. Main outcome measures: The age, the season during which the operation was performed, the time of delivery, the residency, the education, the occupation, the parity, the type of the cesarean section, the complications, the type of anesthesia, the duration of the surgical operation, the Apgar score at the first and the fifth minute, the pH of the umbilical artery, and the adverse effects of the anesthetic agents have been researched and compared. Data are evaluated with a significance level of 0.05. (Ahmet, 2023) The education, occupation, and the residency areas of the two groups were significantly different. In 132 (57.9%) patients, cesarean section was an elective one, and the incidence of use of regional anesthesia in this group was significantly higher than that in the emergency cases. Spinal anesthesia was applied to 101 (45.8%) patients, whereas the other majority received an epidural anesthetic procedure. As for the level at which the agents were injected, there was no significant difference between the spinal and the epidural anesthesia agents that were used. No premature births were particularly detected. During the postoperative 24 hours, 10.5% of the newborns' first Apgar scores were calculated to be lower than 8, but in the fifth minute these rates decreased to 1.3%. The anthropometric data of the patients' height and weight did not display any significantly higher ratios. No statistical differences were detected regarding the pH values of the umbilical arterial blood gases. However, the duration of the anesthetic procedure was significantly longer in the regional group. (Zhang et al.2021)